Ergebnisse der Albanien-Expedition 1961 des Deutschen Entomologischen Institutes. 9. Beitrag. Blattariae. - Princis, Karlis Aleksander (Contributions to Entomology = Beiträge zur Entomologie, 1963)
The present paper represents a study of the Blattariae collected by the Albania expedition of the Deutsches Entomologisches Institut. The whole material contained 65 specimens belonging to 8 species, two of which were new to Albania and one new to the science. Thus the total number of the Blattarian species known from Albania has raised to 9 species. Nomenclatural Acts frieseanus Princis, 1963 (Ectobius), spec. n.